Dampak Atas Kemudahan Fintech Dalam Pinjaman Online Terhadap Karyawan Swasta Di Daerah Serang - Juliyah Juliyah; Indah Mawarni; Muhammad Arif Maulana; Noerma Kurnia Fajarwati (Institut Nalanda, 2024)
In this 5.0 era or the current digital era, new companies have emerged that utilize the development of technology. Fintech is an alternative to online loan financing that is so easy to feel at this time. In addition, the existence of fintech really affects the lifestyle of today's economic society which is so fast and instant, without requiring a complicated process. The ease of online lending is felt by all circles, especially among private employees in Serang, where the needs are increasing from the increasing need for basic necessities for those who are married and the prices of goods are increasing, with these conditions private employees take Fintech online loan financing for their daily needs because of the ease in terms of registration and disbursement which is very fast. From the data that researchers found, there is an increasing financial gap experienced by private employees in Serang, where the ease of fintech (Financial Tecnology) in online loans is very easy without knowing the impact that will be experienced by private employees, and in the end when payday closes the hole digs the hole, meaning that when payday covers debt and credit. Thus the researcher wishes to discuss the ease of fintech in online lending to private employees in the attack area. The method that researchers use is to use descriptive qualitative methods through a descriptive analysis approach that aims to describe the phenomenon to be studied. As one of the procedures in analyzing or investigating by providing a description of the state of the subject or object in the study, it can be in the form of individuals, institutions, society and others, which are based on the facts that exist or are found as they are. The results of this study are In the attack area the majority of companies in payroll for their employees, in collaboration with financial institutions that encourage employees to understand and use fintech. With the ease of fintech itself, many employees fall into online loan financing which results in various impacts, whether from positive or negative impacts, but the development of this technology provides benefits that are very helpful for private employees in meeting their daily needs.